2005
DOI: 10.1016/j.ejheart.2004.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The increase in serum uric acid concentration caused by diuretics might be beneficial in heart failure

Abstract: Patients with mild-moderate chronic heart failure (CHF) often have raised levels of serum uric acid (UA). This is due, amongst other factors, to reduced UA excretion by the kidneys, which is partly explained by restriction of sodium intake and treatment with diuretics. The decline in renal function that parallels worsening cardiac function also contributes to elevated serum UA in patients with advanced CHF. However, UA production also appears to be augmented in CHF. Because UA scavenges various reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 97 publications
1
30
0
Order By: Relevance
“…There are numerous medications that impair renal clearance of uric acid including loop and thiazide diuretics [25] and genetic polymorphisms in anion transporters such as Uric Acid Anion Transporter 1 (URAT-1) may lead to hyperuricemia [26]. Approximately 15% of uric acid clearance is through the GI tract, consequently small bowel disease or altered phenotype can also contribute [27].…”
Section: The Reason For Hyperuricemiamentioning
confidence: 99%
“…There are numerous medications that impair renal clearance of uric acid including loop and thiazide diuretics [25] and genetic polymorphisms in anion transporters such as Uric Acid Anion Transporter 1 (URAT-1) may lead to hyperuricemia [26]. Approximately 15% of uric acid clearance is through the GI tract, consequently small bowel disease or altered phenotype can also contribute [27].…”
Section: The Reason For Hyperuricemiamentioning
confidence: 99%
“…The production of UA by xanthine oxidase also generates free radicals that might adversely affect mitochondrial function and ATP production. XOIs might reduce free radical production, leading to improved left ventricular (LV) function and reverse LV remodeling and renal function 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. There is a substantial literature suggesting that serum UA concentrations are associated with worse cardiovascular outcomes 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…However, UA is excreted by the kidney and therefore a marker of renal function which is also strongly associated with cardiovascular outcome. UA is also an anti‐oxidant 16. Accordingly, there are theoretical reasons why XOI could improve, worsen, or have no effect on cardiovascular outcomes 17…”
Section: Introductionmentioning
confidence: 99%
“…Since UA has strong anti-oxidant properties (Hediger et al 2005;Reyes 2005), a number of investigators have suggested that the reason for selection is that circulating UA strongly and positively affects human resistance to oxidative stress Skalska et al 2005;Reyes 2005;Waring et al 2006). In fact, once differential concentrations are accounted for, the antioxidant power of UA is substantially higher than other non enzymatic antioxidants such as ascorbic acid, α-and γ-tocopherol, β-carotene, and probably also of enzymatic antioxidants such as superoxide dismutase and catalase (Hediger et al 2005).…”
Section: Introductionmentioning
confidence: 99%